The noble gas inventory in metal samples and troilite inclusions from IIIAB iron meteorites: Reinvestigating the live 129I‐129Xe dating method. (19th May 2022) - Smith, Thomas; Leya, Ingo
Abstract: The live 129 I‐ 129 Xe dating technique, which internally corrects for shielding, is particularly well suited for large iron meteorites, for which shielding corrections might be difficult to obtain. In addition, the half‐life of 129 I of 16 Ma would allow the study of the important question of the constancy—or variability—of the galactic cosmic rays over a time scale not covered by other cosmogenic nuclides. Here, we present the results of a noble gas study of metal samples and adjacent troilite inclusions from the four IIIAB iron meteorites Cape York (including Agpalilik), Casas Grandes, Trenton, and Grant. The major result is that we can directly determine 129 Xenc concentrations caused by (live) 129 I decay for Cape York, Casas Grandes, Trenton, and Grant. The 129 Xenc concentrations can be used, if combined to 129 I activity concentrations (not measured by us), to calculate cosmic ray exposure (CRE) ages using the (live) 129 I‐ 129 Xe chronometer. For the light noble gases measured in metal and troilite samples, the new data confirm the earlier estimates of a production rate ratio 21 Necos (troilite)/ 21 Necos (metal) in the range 3.08–3.53. Surprisingly, 38 Arcos in troilite from Agpalilik and Casas Grandes is only, respectively, ~36% and ~44% relative to that in the respective metal phases. Considering that 38 Arcos is only produced from iron but not from sulfur, the 38 Arcos concentration measured in troilite is expected to be ~64% relative to that in adjacent metal, that is, some 38 Arcos is missing. Considering krypton in troilite, only 80 Kr, 82 Kr, and 83 Kr are higher than the blank, likely indicating a spallogenic contribution. On average, ~4.2% of measured 80 Kr, ~2.5% of 82 Kr, and ~11.6% of 83 Kr are spallogenic.